2021
DOI: 10.1016/j.jhepr.2021.100263
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity is associated with reduced risk of liver disease in the prospective UK Biobank cohort

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 35 publications
(43 reference statements)
5
38
0
1
Order By: Relevance
“…LPA, light-intensity physical activity; MVPA, moderate-to vigorous-intensity physical activity; NAFLD, non-alcoholic fatty liver disease; SB, sedentary behaviour preventive effect on incident NAFLD 13 and progression to severe liver disease and mortality in patients with liver disease. 13,43 These studies were conducted in western counties and further prospective studies from Asian countries are required. Second, because alcohol consumption was calculated by a self-administered questionnaire, there could be reporting bias including underevaluation.…”
Section: Ta B L Ementioning
confidence: 99%
See 2 more Smart Citations
“…LPA, light-intensity physical activity; MVPA, moderate-to vigorous-intensity physical activity; NAFLD, non-alcoholic fatty liver disease; SB, sedentary behaviour preventive effect on incident NAFLD 13 and progression to severe liver disease and mortality in patients with liver disease. 13,43 These studies were conducted in western counties and further prospective studies from Asian countries are required. Second, because alcohol consumption was calculated by a self-administered questionnaire, there could be reporting bias including underevaluation.…”
Section: Ta B L Ementioning
confidence: 99%
“…In recent years, the health benefits of light-intensity PA (LPA, ≤2.9 METs) 8,9 and overall MVPA, including sporadic MVPA, 10,11 have been shown. Although a few studies [12][13][14] confirmed the association between accelerometer-measured overall PA and NAFLD, no studies assessed the differences in dose-response associations by PA intensity. Additionally, some of these studies were limited by small sample size 14 and indirect assessment of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ICD codes for cardiovascular disease (CVD) were defined from Lees et al 9 and Tavaglione et al 10 , and self-reported codes used were "angina","heart attack/myocardial infraction", "stroke", "subarachnoid haemorrhage", "brain haemorrhage", "ischaemic stroke" and "heart failure/pulmonary odema". The ICD codes for liver disease were taken from Schneider et al 11 and the self-reported codes used were "liver failure/cirrhosis", "infective/viral hepatitis", "alcoholic liver disease/alcoholic cirrhosis" and "liver/biliary/pancreas problem". The codes for kidney disease were taken from Lin et al 12 and Definitions of End Stage Renal Disease for UK Biobank Phase 1 Outcomes Adjudication (biobank.ndph.ox.ac.uk/ukb/ukb/docs/alg_outcome_esrd.pdf).…”
Section: Disease/physiological Condition Categoriesmentioning
confidence: 99%
“…Treatment options for HCC can be broadly classified into surgical resection and nonsurgical therapies dependent upon the stage of the disease, liver function, availability of donor organs, cost of treatment, and so on [128]. The Westernized diet and sedentary lifestyle promote the progression of NAFLD [129,130]. A cohort study in Europe also showed that physical activity is inversely associated with the risk of HCC [131].…”
Section: Treatment Options Against Hccmentioning
confidence: 99%